School media as a pedagogical activity in the psychological care of the child - AMROUNI TERZOULET, Houria; BENZAAMOUCHE BOUDIAF, Nadia (Social Sciences Journal)
This study aims to provide a vision of a media activity that may in the future form the nucleus of a media program for the psychological support of the schooled child in Algeria, or in other words, we try to deal with the media material as a pedagogical function for the pedagogical specialist on the one hand, and as a personal activity for the child on the other hand, and as Bousna Mahmoud and others indicate that the media process does not stop Rather, it should help the individual to give meaning to the acquired information and integrate it into his personal characteristics by building and developing behavioral knowledge and future knowledge.